PENINGKATAN PROFESIONALISME GURU BAHASA ARAB: UPAYA PENINGKATAN MUTU PEMBELAJARAN BAHASA ARAB - Miswari Miswari (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2010)
Arabic subject is very important as a tool to study and understand Islamic teaching. Arabic is not only important for the student at senior high level, but also for the college student. So, the subject has to be taught by competence teachers or lecturers. There are many ways to be professional as Arabic teacher. Among the ways are teacher should master the Arabic subject, learn more and feel that his knowledge has to be improved every time. Teachers also can improve the quality of learning process based on the standard, understand deeply about learning concept, and improving Arabic language countinously.